Seasonal variations of injury and overtraining in elite athletes - Koutedakis, Y.; Sharp, N. C. (Clinical Journal of Sport Medicine, 1998)
OBJECTIVE: To assess reported injuries and cases of overtraining in relation to training and competition cycles, aerobic versus anaerobic sport, and gender. METHODS: A total of 163 elite male and 94 elite female athletes from eight different sports volunteered. They reported 212 musculoskeletal injuries and 38 cases of the overtraining syndrome. These injuries and cases of overtraining were then arranged according to the training or competition cycle in which they occurred, whether the sufferers were male or female athletes, and the metabolic characteristics of the sports in which the injuries and overtraining occurred. RESULTS: The preparation (October to February), precompetition (March to May), and competition (June to August) cycles were associated with 9%, 19%, and 32% of the injuries reported by the men, respectively, and with 8%, 10%, and 22% of the injuries reported by the women, respectively. For the same cycles, cases of overtraining were found to be 15%, 24%, and 35% for the men, respectively, and 4%, 7%, and 15% for the women, respectively. For both men and women, the competition cycle produced significantly more injuries and incidents of overtraining than the preparation and precompetition cycles (p < 0.05 vs p < 0.005). Similarly, precompetition revealed significantly more injuries (p < 0.05) in men, but not in women, compared with the preparation cycle. Also, male athletes reported a significantly higher number of injuries during the precompetition (p < 0.05) and competition (p < 0.01) cycles, and more cases of overtraining during the competition cycle (p < 0.01) than did their female counterparts. No differences were found when the data were arranged according to dominant metabolic characteristics of the sports in which the injuries and overtraining occurred. CONCLUSIONS: Elite athletes are more likely to become injured or overtrained during the precompetition and, especially, competition cycles than in the preparation cycle. Parallel seasonal variations were also found when data were analyzed for aerobic versus anaerobic sport and gender.